IMPLEMENTASI KEBIJAKAN KUOTA GENDER PARTAI NASIONAL DEMOKRAT (NASDEM) PADA PEMILU LEGISLATIF 2019 - Fifi Puteri Wulandari (2023)
This study aims to discuss the implementation of the Democratic National Party's (NasDem) gender quota policy in the 2019 Legislative Election. Raising the problem formulation regarding how to implement the Democratic National Party's gender quota policy so that it is successful in increasing the number of seats for women's representation in the DPR RI in the 2019 Legislative Election? This study uses the theory of election campaign strategies, gender quota policies, women's representation, and gender responsive political parties. This research uses a qualitative approach with descriptive research types and primary data sources generated through interviews with the DPP NasDem Party, women members of the DPR RI NasDem faction as well as KPP RI officials, KPPI honor council, academics, and coordinators of the success team for winning the 2019 Legislative Election for DPR RI candidates Lisda Hendrajoni. The results of the study show that the NasDem Party has succeeded in implementing the gender quota policy by including 30% women in the central management and 30% women in the nomination of members of the legislature. In carrying out the election campaign, implementing an offensive strategy of expanding the market and penetrating the market was also driven by the internal work programs of the NasDem Party such as NasDem calling, political education for women, NasDem caring for women, and the organizational wing Garnita Malahayati. The gender quota policy implemented by the NasDem Party has succeeded in increasing the number of women's representation in the legislature, the increase in women's representation of the NasDem Party has also succeeded in increasing the performance of elected women members in the legislature. So this research assesses that based on these indicators, the NasDem Party can be said to be a gender-responsive political party..